Recent Advances in Nanopore Technology for Copper Detection and Their Potential Applications - Vaneev, Alexander N.; Timoshenko, Roman V.; Gorelkin, Petr V.; Klyachko, Natalia L.; Erofeev, Alexander S. (Nanomaterials (Basel, Switzerland), 2023)
Recently, nanopore technology has emerged as a promising technique for the rapid, sensitive, and selective detection of various analytes. In particular, the use of nanopores for the detection of copper ions has attracted considerable attention due to their high sensitivity and selectivity. This review discusses the principles of nanopore technology and its advantages over conventional techniques for copper detection. It covers the different types of nanopores used for copper detection, including biological and synthetic nanopores, and the various mechanisms used to detect copper ions. Furthermore, this review provides an overview of the recent advancements in nanopore technology for copper detection, including the development of new nanopore materials, improvements in signal amplification, and the integration of nanopore technology with other analytical methods for enhanced detection sensitivity and accuracy. Finally, we summarize the extensive applications, current challenges, and future perspectives of using nanopore technology for copper detection, highlighting the need for further research in the field to optimize the performance and applicability of the technique.